Organochlorine pesticides and polychlorinated biphenyls in soil and water samples in the northeastern part of São Paulo State, Brazil - Rissato, Sandra Regina [UNESP]; Galhiane, Mario Sergio [UNESP]; Ximenes, Valdecir Farias [UNESP]; de Andrade, Rita M. B.; Talamoni, Jandira Liria Biscalquini [UNESP]; Libanio, Marcelo; de Almeida, Marcos V.; Apon, Benhard M.; Cavalari, Aline A. (Elsevier B.V., 2006)
Detailed analyses of persistent organic pollutants (POPs) such as organochlorine pesticides (OCPs), hexachlorocyclohexane (HCH) isomers (HCHs), dichlorodiphenyltrichloro ethane (DDT) and its metabolites (DDTs) and congeners of polychlorinated biphenyls (PCBs) in soil and surface water from the northeastern São Paulo, Brazil allowed the evaluation of the contamination status, distribution and possible pollution sources. The pesticides and PCBs demonstrated markedly different distributions, reflecting different agricultural, domestic and industrial usage in each region studied. The ranges of HCH, DDT, and PCBs concentrations in the soil samples were 0.05-0.92, 0.12-11.01, 0.02-0.25 ng g(-1) dry wt, respectively, and in the surface water samples were 0.02-0.6, 0.02-0.58 and 0.02-0.5 ng l(-1), respectively. Overall elevated levels of DDT and PCB were recorded in region 2, a site very close to melting, automotive batteries industries, and agricultural practice regions. High ratios of metabolites of DDT to DDT isomers revealed the recent use of DDT in this environment. The sources of contamination are closely related to human activities, such as domestic and industrial discharge, street runoff, agricultural pesticides and soil erosion, due to deforestation as well as atmospheric transport. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: orgeanochlorine pesticides; PCBs; water; soil